The story of Thomas Alva Edison - Meadowcroft, Enid LaMonte 1898-; Stein, Harve 1904-. (New York Grosset & Dunlap, 1952)
A biography of inventor Edison whose discoveries were important to entertainment because he discovered electric lights, motion pictures, and a method of recording the human voice.
Keywords: Edison, Thomas Alva -- 1847-1931.